1998
DOI: 10.1042/bj3300081
|View full text |Cite
|
Sign up to set email alerts
|

DNA recognition by quinoxaline antibiotics: use of base-modified DNA molecules to investigate determinants of sequence-specific binding of triostin A and TANDEM

Abstract: The methodology of DNAase I footprinting has been adapted to investigate the sequence-specific binding of two quinoxaline drugs to DNA fragments containing natural and modified bases. In order to help comprehend the molecular origin of selectivity in the bis-intercalation of triostin A and TANDEM at CpG and TpA sites respectively, we have specifically examined the effect of the 2-amino group of guanine on their sequence specificity by using DNA in which that group has been either removed from guanine, added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…As expected, due to the reported ascendancy of the exocyclic 2-amino group in the binding of these compounds, it was found that replacement of all Gs by Is resulted in triostin A (25), echinomycin (26) and 2QN (10) completely failing to bind to these modified nucleotides. Strikingly, however, replacing all As with Ds led to an unexpected redistribution of binding sites for echinomycin (23) and 2QN (10) to other pyrimidine–purine combinations, such as TpD and CpD, in preference to the usual CpG step despite the fact that, from a minor-groove viewpoint, CpG and TpD steps share the same hydrogen bonding capabilities (Figure 2).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…As expected, due to the reported ascendancy of the exocyclic 2-amino group in the binding of these compounds, it was found that replacement of all Gs by Is resulted in triostin A (25), echinomycin (26) and 2QN (10) completely failing to bind to these modified nucleotides. Strikingly, however, replacing all As with Ds led to an unexpected redistribution of binding sites for echinomycin (23) and 2QN (10) to other pyrimidine–purine combinations, such as TpD and CpD, in preference to the usual CpG step despite the fact that, from a minor-groove viewpoint, CpG and TpD steps share the same hydrogen bonding capabilities (Figure 2).…”
Section: Introductionsupporting
confidence: 59%
“…TANDEM does not bind to CpI steps) (25) and, similarly, that binding of CysMeTANDEM to CpI is much weaker than binding to the high-affinity TpA sites (16) despite the fact that the minor grooves of CpI and TpA steps provide the same hydrogen bonding possibilities (Figure 2). Furthermore, the affinity of CysMeTANDEM (21,22) and TANDEM (8,18) for binding TpA-containing sequences is clearly affected by the flanking bases, with the tetranucleotides ATAT and TTAA being the best and poorest binding sites, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the binding is strongly influenced by the identity of the surrounding bases and all TpA steps do not constitute good binding sites. This is not unexpected since other studies have shown that TANDEM does not bind to IpC, for which the hydrogen bonding face exposed to the minor groove is identical to TpA (18). It has therefore been suggested that the selectivity is not determined by hydrogen bond formation but may originate from steric and/or hydrophobic interactions with a minor groove of suitable dimensions (18).…”
Section: Discussionmentioning
confidence: 85%
“…Subsequent footprinting studies showed that TANDEM and its derivative [N-MeCys 3 ,N-MeCys 7 ]TANDEM bind to the dinucleotide TpA (8 -11), and this has been confirmed by NMR studies which have suggested mechanisms by which the ligand targets this sequence (12)(13)(14)(15)(16). However, several studies have suggested that TpA alone does not constitute the best binding sequence, and that the preferred sites are flanked by other AT residues (8,9,17,18), consistent with the observation that the ligand binds cooperatively to poly(dA-dT) (7). We have therefore analyzed the binding of this ligand to TpA when flanked by different base pairs, by quantitative DNase I footprinting using a novel DNA substrate which contains all possible 136 tetranucleotide sequences.…”
mentioning
confidence: 77%